NFC and VLC based Mobile Business Information System for Registering Class Attendance - Rios-Aguilar, Sergio; Sarría, Íñigo; Beltrán Pardo, Marta (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
This work proposes a Mobile Information System for class attendance control using Visible Light Communications (VLC), and the students’ own mobile devices for automatic clocking in and clocking out. The proposed information system includes (a) VLC physical infrastructure, (b) native Android and iOS apps for the students, and (c) a web application for classroom attendance management. A proof of concept has been developed, setting up a testbed representing a real-world classroom environment for experimentation, using two VLC-enabled LED lighting sources. After three rounds of testing (n=225) under different conditions, it has been concluded that the system is viable and shows consistent positive detections when the smartphones are on the classroom desk within non-overlapped areas of the light circles generated by the LED lighting sources on the table surface. The performed tests also show that if mobile devices are placed within those overlapping areas, the likelihood of a detection error could increase up to nearly 10%, due to multipath effects, and actions can be taken should it happen. Finally, it has to be highlighted that the proposed autonomous class attendance system allows lecturers to focus on making the most of their time in class, transferring knowledge instead of spending time in attendance management task.
Keywords: education; presence control; visible light communications; near field communication; IJIMAI